Human Trafficking within Southeast Asia’s Online Gambling Industry: International Resilience and Policing Challenges - Rofii, Muhammad Syaroni; Ardiyansah, Ruben Firman (Jurnal Ilmu Kepolisian, 2026)
Human trafficking has become a major concern for the Indonesian government, especially over the last five years, due to the increasing number of cases involving Indonesian citizens. Current trafficking patterns differ from earlier forms because they are increasingly shaped by digital recruitment, ASEAN mobility, and the use of online gambling and online scam operations as a cover for exploitation. This study examines the factors behind the growing number of trafficking cases, the relationship between online gambling and human trafficking targeting Indonesian citizens in Southeast Asia, and the law enforcement challenges faced in addressing this crime within the framework of ASEAN cooperation. This research applies a qualitative case study approach. Data were collected through structured interviews with informants who have direct knowledge of cross-border mobility and victim handling, including police attachés and Indonesian diplomats in Thailand, Malaysia, and the Philippines. These data were supported by field observations at major mobility hubs, particularly international airports, and by secondary data from the Indonesian National Police, the Ministry of Foreign Affairs, and the Ministry for the Protection of Indonesian Migrant Workers. The findings show that domestic economic pressures make young people vulnerable to deceptive job offers promising high salaries. At the same time, trafficking syndicates exploit regulatory gaps and weak oversight in several countries. In law enforcement, eradication efforts remain constrained by the uneven commitment of ASEAN member states to fully implement the principles of ACTIP. As a result, bilateral cooperation is often considered more effective than regional mechanisms in repatriating victims. This study contributes to understanding recruitment patterns and trafficking networks and provides a basis for strengthening national and regional policy responses.